Immunomodulatory effect of tea mistletoe (Scurrula oortiana) extract on chicken embryos - S Murtini; R Murwanti; F Satrija; E Handharyani (Jurnal Ilmu Ternak dan Veteriner, 2006)
Tea mistletoe is one of medicinal herb which believed has an anticancer activity, it’s due to the capability of immunostimulator. The following research was carried out to determine the immunomodulatory effect of tea mistletoe (Scurrula oortiana) extract on chicken embryos. Twenty White Leghorn Specific Pathogen Free (SPF) 10 days old embryonated chicken eggs were divided into four groups of 5 eggs. The first group served as control and they were inoculated with aquabidestilate sterile. The second, third and fourth group was inoculated with 0.1 mg, 0.2 mg, and 0.4 mg S. oortiana extract/egg respectively. S. oortiana extract was inoculated via allantoic cavity. All experimental eggs were incubated at 37oC until day 21 and incubation was terminated before the embryos hatched. The embryos and the lymphoid organs (bursa of Fabricius, thymus and spleen) were weighed. Immunomodulatory effect of tea mistletoe extract was measured by counting the percentage of bursa of Fabricius active lymphoid follicle and the area of thymus medulla. The results showed tea mislestoe extract at the dose of 0.1mg, 0.2 mg and 0.4 mg have immunomodulatory effect on chicken embryos indicated by the increase of percentage of active lymphoid follicle of bursa Fabricius i.e. 68.8, 71.8 and 57.8% and increase area of thymus medulla i.e. 24.9 – 39.3% respectively compared to control group i.e. 22.6% of active lymphoid follicle of bursa Fabricius and 17.6% of thymus medulla area. It is concluded that S. oortiana extract at the dose of 0.1mg, 0.2 mg and 0.4 mg have immunomodulatory effect on chicken embryos.Key Words: Scurrula oortiana, Tea Mistletoe, Embryonated Chicken Egg, Immunomodulator